Maxillofacial Surgery and Craniofacial Deformity Practices and Updates - Ahmad Almasri, Mazen; Kummoona, Raja (IntechOpen, 2020)
The aim of the book "Maxillofacial Surgery and Craniofacial Deformity - Practices and Updates" was to collect various aspects of facial and cranial deformities in one single textbook in order to have a systematic way of thinking when approaching these interconnected manifestations. Furthermore, other associated social aspects of health care are integrated to give a wider view of the problem and some important considerations of care.